Neuropsychopharmacological evaluation of noni (Morinda Citrifolia Linn.) unripe fruit extract in rodents / Megala Narasingam - Megala, Narasingam (2019)
Noni (Morinda citrifolia Linn.) fruit provides a plethora of exciting research avenues to be explored due to its vast therapeutic benefits which includes neuropsychiatric diseases. A systematic approach was designed for extraction of methanolic extract of Morinda citrifolia (MMC) unripe fruit and quantification of phytochemical markers, revealed presences of scopoletin and rutin. It is widely accepted that abnormalities in dopaminergic neurotransmission plays a key role in the pathogenesis of psychosis. MMC (1, 3, 5, 10 g/kg, p.o) dose-dependently attenuated the climbing and stereotyped behaviour induced by apomorphine and methamphetamine, respectively, affirming the antidopaminergic effect of Morinda citrifolia and suggesting antipsychotic-like activity. This study was expanded to improve the understanding of the potential antidopominergic activity of MMC and its biomarkers using isolated rat vas deferens. This study results revealed MMC exhibited a biphasic effect on dopaminergic system, that is, antidopaminergic effect at lower dose (< 40mg/mL) and dopaminergic agonistic effect at higher dose (>60mg/mL). Furthermore, antidopaminergic activity of scopoletin (1-200µg/mL) and rutin hydrate (0.6-312.6 µg/mL), respectively, was established. In order to strengthen the biphasic effect of MMC on dopaminergic system, ethyl acetate fraction Morinda citrifolia (EA-MMC) was subjected to in vivo psychosis mouse models. This study results revealed EA-MMC at a low dose (25 mg/kg, p.o.) significantly attenuated the apomorphine-induced climbing behaviour and methamphetamine-induced stereotyped behaviour in mice. Meanwhile, EA-MMC showed a v dopaminergic agonistic activity at a high dose (3000 mg/kg, p.o.), which was evident from alleviation of haloperidol-induced catalepsy in mice. Following successful establishment of antidopaminergic activity of MMC, the subsequent study was designed to investigate the effect MMC on the rewarding effect of heroin in the rat conditioned place preference (CPP) paradigm and naloxone-precipitated withdrawal in mice. The CPP test results revealed that acute administration of MMC (1, 3, and 5 g/kg, p.o.), 1 h prior to the CPP test on the 12thday significantly reversed the heroin-seeking behaviour. On the other hand, MMC (0.5, 1, and 3 g/kg bw, p.o.) did not attenuate the heroin withdrawal jumps precipitated by naloxone. Finally, the exact dose-dependent effect and underlying mechanisms are not clear with respect to anxiolytic and antidepressant activities. On that account, we investigated the effect of MMC against anxiety using mouse elevated plus maze (EPM); light/dark tests (LDT) and against depression using tail suspension test (TST). The administration of MMC (1 g/kg, p.o.) and diazepam (1 mg/kg, i.p.) significantly attenuated anxiety-like behaviour. Further mechanistic studies revealed the pre-treatment with flumazenil (6 mg/kg, i.p.) or bicuculline (3 mg/kg, i.p.) or WAY 100635 (1 mg/kg, i.p.) antagonized the anxiolytic- like effect elicited by MMC. These results suggest the possible involvement of benzodiazepine-GABAAergic and serotonergic mechanisms in the anxiolytic-like effect of noni fruit. Meanwhile, in the antidepressant study, the administration of MMC (0.5 and 0.75 g/kg, p.o.) and desipramine (30 mg/kg, i.p.) significantly reduced the duration of immobility in TST. Furthermore, pre?treatment of mice with (PCPA; 100 mg/kg, i.p.) for four consecutive days or a single dose of WAY 100635 (1 mg/kg, i.p.) or (AMPT; 100 mg/kg, i.p.) significantly reversed the anti?immobility effect of MMC in TST by indicating the specific involvement of the serotonergic and noradrenergic systems in the antidepressant-like effect of noni. vi Taken together, this PhD research work provides the therapeutic possibilities of Morinda citrifolia fruit extract in the treatment of psychosis, drug dependence, anxiety and depression. Keywords: Noni, neuropsychiatric diseases, dopamine, biphasic effect